Effects of Ramipril and Telmisartan on Plasma Concentrations of Low Molecular Weight and Protein Thiols and Carotid Intima Media Thickness in Patients with Chronic Kidney Disease - Zinellu, Angelo (Hindawi Publishing Corporation, 2016)
Hypertension, a common feature in chronic kidney disease (CKD), is an independent risk factor for CKD progression and cardiovascular disease. Although inhibitors of the renin-angiotensin system (RAS) exert salutary effects on blood pressure control and proteinuria in CKD patients, their activity towards traditional and novel oxidative markers is largely unknown. We studied the effects of 6-month treatment with telmisartan versus a combination of telmisartan and ramipril on plasma concentrations of low molecular mass (LMW, including homocysteine and cysteine) and protein thiols (PSH) plasma concentration and their relationships with carotid intima media thickness (IMT), in 24 hypertensive CKD patients (age 60 ± 12 years, 8 females and 16 males). Pretreatment PSH concentrations were independently associated with IMT (r = −0.42, p = 0.039). Neither treatment affected plasma LMW thiols, in both reduced and total form. By contrast, both treatments increased PSH plasma concentrations and reduced IMT, although significant differences were only observed in the combined treatment group. Our results suggest that the beneficial effects of combined RAS inhibitor treatment on IMT in hypertensive CKD patients may be mediated by a reduction of oxidative stress markers, particularly PSH.